ISLAMIC AND WESTERN HYBRID SYMBOLS IN CONTEMPORARY MOSQUE ARCHITECTURE IN INDONESIA'S REFORM ERA - Putri Suryandari; Jamhari Jamhari; Ahmad Shahid (Journal of Islamic Architecture, 2023)
In Indonesia, there is an ongoing trend toward a rise in modern mosque architecture without domes and traditional identity. Although contemporary mosque architecture is increasing in Indonesia and the world, the concept still generates debate among Islamic society and intellectuals. This study aims to analyze how the conception of symbols and meaning, the architectural style of contemporary mosques in the Indonesian Reformation Era can be accepted by society. The study method is qualitative, by applying library and research field studies. Procedure data collection using method interview, observation, and documentation. The objects of his research are the Assamawaat Mosque-Tangerang, Muhammadiyah PP A-Tanrim Mosque-Central Jakarta, Jami' Darussalam Mosque-Central Jakarta, Al Azhar Bekasi Mosque, Asmaul Husna Bekasi Mosque, Al Safar KM88 Mosque-Cipularang, Merapi Mosque-Jogyakarta, Al Ikhlas Mosque /Honeycomb-Sidoarjo's. This research applied the theory of Roland Bartes semiotic approach; the sacred and profane meaning, Charles Jenks theory to obtain the Symbol Theory of contemporary mosque architectural styles in the Indonesian reform era, and Sayyed H Nasr for Philosophy of Islamic architecture. The findings and results of the study are Contemporary Mosque Architecture in Indonesia, Symbolizing the Hybrid of Islam, and the West. So, Islamic and Western cultures live and develop well in Indonesia. I recommend the results of this research to architectural practitioners, academics, and the public to be applied to contemporary mosque designs.